2012
DOI: 10.1371/journal.pone.0031986
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Related High-Risk Behaviors among Chinese Migrant Construction Laborers in Nantong, Jiangsu

Abstract: BackgroundHIV transmission in rural areas of China is being fueled in part by migrant workers who acquire HIV outside of their hometowns. Recent surveillance statistics indicate that HIV prevalence among returning migrants has increased significantly.MethodsWe conducted a community-based cross-sectional study to assess HIV-related knowledge, attitudes and behaviors among migrant returnees in Nantong, Jiangsu Province, one of the largest exporters of migrant laborers.ResultsA total of 1625 subjects were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 19 publications
5
34
5
Order By: Relevance
“…Xi’an is the capital city of Shaanxi Province while Lantian County is in the territory of Shaanxi Province. Previous studies have demonstrated that rural migrants working in places farther from home have the higher incidence of high-risk behavior compared with those working closer to home [13,14,15]. Therefore, in the present study, the incidence of high-risk behavior in the migrants was clearly lower than that reported in migrants working in Shanghai, Beijing, or Guangzhou.…”
Section: Discussioncontrasting
confidence: 60%
“…Xi’an is the capital city of Shaanxi Province while Lantian County is in the territory of Shaanxi Province. Previous studies have demonstrated that rural migrants working in places farther from home have the higher incidence of high-risk behavior compared with those working closer to home [13,14,15]. Therefore, in the present study, the incidence of high-risk behavior in the migrants was clearly lower than that reported in migrants working in Shanghai, Beijing, or Guangzhou.…”
Section: Discussioncontrasting
confidence: 60%
“…Inconsistent with recent studies conducted in other Western countries of Chinese migrant college students [23], but similar to the findings of previous studies in Hong Kong [24,25], the attitudes of adolescents in this study were less tolerant of premarital intercourse. One possible explanation is that there are cultural differences among adolescents growing up in Hong Kong in comparison to those in Western countries.…”
Section: Discussionsupporting
confidence: 88%
“…The HIV/AIDS knowledge of respondents was generally low same as determined in the works of Arora et al (2014), Qu et al (2008), Purwaningsih et al (2015) and Bowen et al (2016a) contrary to those of Pant et al (2013), Akinola et al (2013), Haupt et al (2005) and Kanda et al (2009).The disparity in the findings of HIV knowledge in the current study and previous studies is mostly influence by the indicators assessed. Risky sexual behaviours were generally low which supports the studies of Akinola et al (2013) and Purwaningsih et al (2015) but contradicts the works of Kassa et al (2013), Arora et al (2014), Haupt et al (2005), Qu et al (2008) and Zhuang et al (2012). Furthermore, there is no statistical significance difference across groupings (i.e.…”
Section: Discussioncontrasting
confidence: 50%
“…The construction industry is particularly vulnerable to the epidemic because of its migrant labour force, large unskilled labour force and aging workforce amongst other reasons (Harinarain & Haupt, 2014). The HIV prevalence rates are increasing in many rural areas in which a significant proportion of the population migrates for work (Zhuang et al, 2012). The ILO (2008) explains that many studies have identified construction workers as a risk group along with miners and transport workers because many of them are mobile workers, with poor living and working conditions, and often separated from their families.…”
Section: 2the Context Of Hiv/aids In the Construction Industrymentioning
confidence: 99%
See 1 more Smart Citation